Implementasi Pendidikan Karakter Religius di Madrasah Ibtidaiyah Negeri 3 Purworejo - Siti Sofiah (LPPM Institut Agam Islam Nahdlatul Ulama (IAINU) Kebumen, 2022)
This research is based on the importance of religious character education in madrasa. In this connection, this study aims to determine the implementation of religious character education at MIN 3 Purworejo. This research is a qualitative research. Data collection uses interviews, observation, and documentation, and the validity of the data uses triangulation, and data analysis techniques include data collection, data reduction, data presentation, and conclusions drawing. This study produces the following conclusions. (1) The values ​​that are internalized in shaping the religious character of students in MIN 3 Purworejo namely Religious, Honest, Tolerance, Discipline, Hard Work, Creative, Independent, Democratic, Curiosity, National Spirit, Love Homeland, Respect Achievements, Friendly / Communicative, Love Peace, Love to Read, Care for the Environment, and Care for Social, and Responsibility; (2) How to instill the values ​​of religious character education in MIN 3 Purworejo namely by: (a) Integrating religious character through the learning process, and through school extracurricular activities, as well as through the involvement of students directly or with giving motivation. (b) Values ​​and Morality Modeling, where the principal of the madrasa, all teachers and employees are the models for others. All madrasa citizens realize that their behavior becomes a model for the character of students. Therefore, all madrasa citizens always try to be careful in their behavior and speaking in front of students. (c) Facilitating values ​​and morality, where this is done by providing opportunities for students to solve problems related to activities in madrasah. The principal, teachers, and employees always listen seriously to the complaints and suggestions of students.